UNIT 17.16 Diagnosing Lysosomal Storage Disorders: The GM2 Gangliosidoses. (1st October 2014) - Hall, Patricia; Minnich, Sara; Teigen, Claire; Raymond, Kimiyo
Abstract: The GM2 gangliosidoses are a group of autosomal recessive lysosomal storage disorders caused by defective β‐hexosaminidase. There are three clinical conditions in this group: Tay‐Sachs disease (TSD), Sandhoff disease (SD), and hexosaminidase activator deficiency. The three conditions are clinically indistinguishable. TSD and SD have been identified with infantile, juvenile, and adult onset forms. The activator deficiency is only known to present with infantile onset. Diagnosis of TSD and SD is based on decreased hexosaminidase activity and a change in the percentage of activity between isoforms. There are no biochemical tests currently available for activator deficiency. This unit provides a detailed procedure for identifying TSD and SD in affected individuals and carriers from leukocyte samples, the most robust sample type available. Curr. Protoc. Hum. Genet . 83:17.16.1‐17.16.8. © 2014 by John Wiley & Sons, Inc.